Political godfathers in Nigeria : a study of Anambra State, 1999-2006 - Ndukwe, Thaddeus Chijioke (2011)
In this study, I have examined the pro et contra arguments on the role of political godfathers in the political process of Anambra State, Nigeria, during the period 1999 to 2006. I have used extensive interviews and a small survey in addition to existing texts in this regard. In the process, two broad camps of arguers are discovered, namely, the anti- and pro-godfather camps. While the pro-godfathers argue in pro, using the concepts of social philanthropy and political pedagogy as a rhetorical framework to describe political godfatherism as patriotic, democratic and prodevelopment that should be promoted and permanently embedded in the Nigerian constitution, the anti-godfathers argue in contra, using the concepts of electoral manipulation, candidate imposition and political violence as a rhetorical framework to depict it as unpatriotic, undemocratic and anti-development that should be criminalized and abolished in Nigeria. To deepen analysis and put this study in its specific methodological perspective, I have used political theory and its sub-category, rhetorical theory, inspired mainly by Robert Michels, Pekka Korhonen, Chaim Perelman, and Roderick Hart, among others. In the end, I discovered that while some of the respective claims of the anti- and progodfathers have been true, some others have been overtly or covertly exaggerated, or are outright lies. For instance, while it seems true that some political godfathers do indulge, or may have indulged, in political pedagogy and social philanthropy to assist the poor, especially poor politicians, naive political aspirants or political dilettantes, they and/or some others sometimes appear to do so for hidden or outright selfish agenda, namely, financial and political interests, which it has been argued, often exploit the political and economic structures of Anambra State to the detriment of the people. Because of this, I distinguish between two kinds of political godfatherism, namely, patriotic and parasitic. I then propose that to promote and sustain the former, as well as discourage and uproot the latter, in the political process, a legalistic solution is inevitable. That is to say, a law would need to be enacted to specify formal guidelines for political godfathers and punishments for any defaulter(s) in Nigeria.